Women Leaders in a Predominantly Male-Dominated Society: Mexico. (May 2016) - Moreno, Patricia; McLean, Gary N.
The Problem: This qualitative (phenomenological) study focused on gaining a deep understanding of the experiences of women leaders in Mexico, a predominantly male-dominated culture. Seven women leaders were interviewed to share their personal experiences, reflections, feelings, ideas, and actions related to their leadership positions in different arenas, such as corporate, political, academic, and non-profit organizations. The Solution: We conducted a thematic analysis of the transcribed interviews to discover commonalities among the experiences of the participants. The analysis revealed six themes: academic preparation is necessary, there are innate characteristics, decisions are made under principles and ethical values, the job itself is very important, the goal is to find a balance between personal and professional time, and the leadership position gives benefits. The Stakeholders: This research has implications for human resource development (HRD) practitioners, academics, and executives. HRD practitioners can design more effective interventions, deliver more effective training and leadership programs, and provide opportunities focused on women interested in reaching top executive positions. This research suggests the importance of future research, both qualitative and quantitative in Mexico, focusing on research of women, Mexican women, and Mexican women leaders.